Effect of Artemisia vulgaris Extract for Increasing IL-12 and Granzyme Expression (Study on Mammary Adenocarcinoma C3H Mice Given Adriamycin- Cyclophosphamide Chemotherapy Regimen) - Hardanto, Gery Rifano; Selamat Budijitno (Biomedical Journal of Indonesia, 2021)
Background: The incidence of breast cancer worldwide is still high. Surgery remains the top choice with other modalities of chemotherapy, radiation, and immunotherapy such as Artemisia vulgaris (AV). The study was aimed to demonstrate that administration of AV extract increased p53 expression and the apoptotic index in mammary adenocarcinoma. Methods: This study used a "Post-test only control group design" on 24 females C3H mice that were randomly selected and divided into four groups: group K (control), P1 (chemotherapy), P2 (extract), and P3 (combination). Mammary adenocarcinoma comes from the inoculation of donor mice. Chemotherapy of Adriamycin 0,18 mg and Cyclophosphamide 1,8 mg were given in 2 cycles. AV 13 mg (0.2 ml) was given once daily orally. IL-12 and granzyme expression were evaluated by immunohistochemical staining. Results : Mean of IL-12 and Granzyme expression were found in groups K, P1, P2, P3 were 50,40 ± 1,56, 60,28 ± 1,54, 53,48 ± 1,35, 75,40 ± 1,46 dan 14,96 ± 0,61, 24,86 ± 1,21, 17,14 ± 1,02, 26,62 ± 0,70. The statistical analysis showed that there were significant differences in the IL-12 between groups of K vs P1 (0,001), P1 vs P2 (0,001), K vs P2 (0,028), P1 vs P3 (0,001), K vs P3 (0,001), P2 vs P3 (0,001) and in granzyme expression between groups of K vs P1 (0,001), P1 vs P2 (0,001), K vs P2 (0,010), P1 vs P3 (0,047), K vs P3 (0,001), P2 vs P3 (0,001). Correlation analysis between IL-12 and Granzyme expression were found significant correlation (p = 0,001 and r = -0,911). Conclusion: Artemisia vulgaris can improve the effectivity of Adriamycin-Cyclophosphamide chemotherapy on C3H mice with mammary adenocarcinoma in terms of elevated IL-12 and Granzyme expression.